Termination of Hajj Initial Deposit Financing Products for Hajj Pilgrimage Organization Costs: Normative Legal Analysis - Taufiq, M; Sari, Dewi Puspita; Ridho, Ali; Sobri, Irwan Mohd; Alexander, Ongky; Ilham, Muhammad (SHAHIH: Journal of Islamicate Multidisciplinary, 2024)
The authority to regulate Hajj initial deposit financing products in Islamic banking between OJK as a regulator and supervisor of financial institutions and the Ministry of Religion as the organizer of Hajj in Indonesia is interesting to study. The research aims to find efforts to harmonize the law of Hajj initial deposit financing in Tanjungpinang city for legal certainty in the community and contribute to the improvement of maslahah policies.  The research is a normative qualitative-legal research and the data is obtained through interview techniques and a collection of documents in the form of books and reputable scientific articles. The findings in the study are first, the practice of financing the initial deposit of Hajj in Tanjungpinang City was carried out by Bank Muamalat KC Tanjungpinang with the Pro Hajj multipurpose product in August 2020, then stopped because it violated the rules of the Indonesian Ministry of Religion and was replaced with the Pro Hajj Plus product. Second, harmonization of regulations is a must to be carried out with regulations from the OJK considering that the authority to regulate and supervise Islamic banking is with the OJK not the Ministry of Religion.